Upaya Meningkatkan Hasil Belajar Kognitif Kimia Siswa dengan Menggunakan Metode Latihan (Drill) - Evasari Kristiani Lase; Friska Juliana Purba (Universitas Indraprasta PGRI Jakarta, 2020)
Results of cognitive learning of students in one of the schools in Lampung towards the chemistry lesson for the 2019/2020 school year showed less satisfactory. Out of a total of 9 grade XI IPA students, 5 students have not been able to reach the KKM because of the lack of students’ learning experience that has an impact on the low cognitive outcomes. Teachers overcome this problem by implementing the drill method. Chemical variation work requires a lot of practice. This article aims to expose the exercise methods to the implementation of students learning experiences and to improve student's cognitive learning outcomes. The methodology used was a literature study by collecting all references to issues that had been analyzed through mentor feedbacks and teacher teaching reflections. Literature studies showed that exercise method could help improve student's cognitive learning outcomes by following the implementation procedures of existing method. The exercise method looked at the students having each potential that needed to be trained and developed with the following implementation steps: 1). Teachers conveyed the purpose of learning. 2). Teachers provided motivation for learning. 3). Teacher provided material explanations with examples of questions. 4). The teacher checked the students ' understanding and gave the opportunity to ask. 5). The student did the exercise questions given by the teacher. 6). The exercise questions were discussed together by the teacher and the students as well as emphasized the concept of material that had not been masteredby students.